MAGNETIC ANOMALY PATTERNS USING TREND SURFACE ANALYSIS APPLICATION (TSA) ON MARINE GEOLOGY MAPPING IN THE BALIKPAPAN WATERS - Delyuzar Ilahude (Marine Geological Institute of Indonesia, 2012)
The application of Trend Surface Analysis (TSA) method an geological and geophysical research in map sheets 1813-1814, Balikpapan Waters and its surrounding, shows the significant value of residual anomaly. The magnetic disseverance of regional and total anomaly value obtained the negative anomaly between -50 nT and -350 nT and positive anomaly between +50 nT and +400 nT. The contour of total and regional anomaly shows the magnetic properties of rocks which characterizes the geological arrangements of the research areas. Residual anomaly yielded from the 2nd order value of regional anomaly might be correlated with the formation of basin structures in the central and northern parts of research area, which is interpreted as a part of Kutai Basin. Keywords : TSA method, magnetic anomaly, geology and geophisics, Balikpapan Waters. Penerapan metode TSA dalam penelitian geologi dan geofisika di Lembar Peta 1813-1814, Perairan Balikpapan dan sekitarnya menunjukkan nilai anomali sisa yang cukup signifikan. Hasil pemisahan nilai anomali magnet regional dan anomaly total diperoleh nilai anomali yaitu antara -50 nT dan –350 nT dan anomali positif antara +50 nT dan +400 nT. Kontur anomali total dan anomali regional memperlihatkan sifat kemagnitan batuan yang mencirikan tatanan geologi daerah penelitian. Anomali sisa dihasilkan dari nilai anomali regional orde ke 2, kemungkinan berkaitan dengan pembentukan struktur cekungan di bagian tengah dan utara daerah penelitian yang ditafsirkan sebagai bagian dari Cekungan Kutai. Kata kunci : metode TSA, anomali magnet, geologi dan geofisika, Perairan Balikpapan.